Compact substrate integrated waveguide transversal filter with mixed source–load coupling. Issue 2 (22nd January 2016) - Sun, Peng-fei; Shen, Wei; Wu, Liang; Qian, Rong; Sun, Xiao-wei
Abstract : This study proposes a compact implementation of substrate integrated waveguide (SIW) transversal filter with mixed source and load coupling. One dual-mode microstrip resonator, etched on the top metal layer of SIW cavity, is utilized to achieve transversal topology. Therefore, four transmission zeros can be obtained by introducing mixed sourced and load coupling, which is realized by inter-digital slot structure. A third-order SIW transversal filter sample is fabricated using printed circuit board technology, and its measured S-parameters have good agreements with the simulated ones.